2022
DOI: 10.3390/ijms23126600
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Menthol and Thymol Derived Ciprofloxacin: Influence of Structural Modifications on the Antibacterial Activity and Anticancer Properties

Abstract: Sixteen new Ciprofloxacin derivatives were designed and successfully synthesized. In an in silico experiment, lipophilicity was established for obtained compounds. All compounds were screened for antimicrobial activity using standard and clinical strains. As for Gram-positive hospital microorganisms, all tested derivatives were active. Measured MICs were in the range 1–16 µg/mL, confirming high antimicrobial potency. Derivative 12 demonstrated activity against all standard Gram-positive Staphylococci, within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Nevertheless, it's worth noting that multiple interactions with bacterial cells contribute to their antimicrobial activity. In previous 10 and current studies, menthol and thymol moieties were chosen for several interactions with bacterial cells, such as: damage to membrane proteins, reduced ATP synthesis, increased membrane permeability and membrane fluidity causing leakage of ions, a decrease in the pH gradient across the cytoplasmic membrane 11 , 12 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, it's worth noting that multiple interactions with bacterial cells contribute to their antimicrobial activity. In previous 10 and current studies, menthol and thymol moieties were chosen for several interactions with bacterial cells, such as: damage to membrane proteins, reduced ATP synthesis, increased membrane permeability and membrane fluidity causing leakage of ions, a decrease in the pH gradient across the cytoplasmic membrane 11 , 12 .…”
Section: Resultsmentioning
confidence: 99%
“…For this study, we have picked Ciprofloxacin over Gatifloxacin as starting material, although both possess accessible piperazinyl moiety. Our previous examination indicated that thymol and menthol Ciprofloxacin derivatives showed promising antibacterial activities and low toxicity to eukaryotic cells 10 . Encouraged by the results, we have decided to continue our study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations